Fodder and grain yield of barley (Hordeum vulgare L.) as influenced by nitrogen doses and varieties. - Neetarani, S.; Luikham, E.; Anal, Ps. M. (Indian Journal of Hill Farming, 2018)
Field experiment was conducted during the rabi season of 2010 – 11 to find out the response of promising barley varieties to nitrogen under acidic soil condition of Manipur. The crop was sown on 28th November, 2010, cut for green fodder on 4th February, 2011 and finally the grain harvested on 20th April, 2011. The total rainfall received during the cropping season was 463 mm. The result revealed that among the varieties, BHS-380 showed significantly higher fresh and dry weight of the plant as well as the number of tillers per plant. Remarkably higher green and dry fodder was recorded in this variety with the application of 60 kg N/ha. The number of effective tillers, number of grains per panicle and panicle length recorded significantly higher in the variety HBL – 276 with the application of nitrogen up to 60 kg/ha. Significant increase in grain yield of barley was also observed in the same treatment. Highest profit could be obtained from the variety HBL-276 with the application of 60 kg N/ha.